Management of patients with rectocele, multiple pelvic floor dysfunctions and obstructed defecation syndrome - Murad-Regadas,Sthela Maria (2012)
CONTEXT: Management of patients with obstructed defecation syndrome is still controversial. OBJECTIVE: To analyze the efficacy of clinical, clinical treatment followed by biofeedback, and surgical treatment in patients with obstructed defecation, rectocele and multiple dysfunctions evaluated with echodefecography. METHODS: The study included 103 females aged 26-84 years with obstructed defecation, grade-II/III rectocele and multiple dysfunctions on echodefecography. Patients were distributed into three treatment groups and constipation scores were assigned. Group I: 34 (33%) patients with significant improvement of symptoms through clinical management only. Group II: 14 (14%) with improvement through clinical treatment plus biofeedback. Group III: 55 (53%) referred to surgery due to treatment failure. RESULTS: Group I: 20 (59%) patients had grade-II rectocele, 14 (41%) grade-III. Obstructed defecation syndrome was associated with intussusception (41%), mucosal prolapse (41%), anismus (29%), enterocele (9%) or 2 dysfunctions (23%). The average constipation score decreased significantly from 11 to 5. Group II: 11 (79%) grade-II rectocele, 3 (21%) grade-III, associated with intussusception (7%), mucosal prolapse (43%), anismus (71%) or 2 dysfunctions (29%). There was significant decrease in constipation score from 13 to 6. Group III: 8 (15%) grade-II rectocele, 47 (85%) grade-III, associated with intussusception (42%), mucosal prolapse (40%) or 2 dysfunctions (32%). The constipation score remained unchanged despite clinical treatment and biofeedback. Twenty-three underwent surgery had a significantly decrease in constipation score from 12 to 4. The remaining 32 (31%) patients which 22 refused surgery, 6 had low anal pressure and 4 had slow transit. CONCLUSIONS: Approximately 50% of patients with obstructed defecation, rectocele and multiple dysfunctions presented a satisfactory response to clinical treatment and/or biofeedback. Surgical repair was mainly required in patients with grade-III rectocele whose constipation scores remained high despite all efforts.